PELATIHAN YOGA CHILD POSE SEBAGAI UPAYA PEMBERDAYAAN REMAJA DALAM MENGATASI DISMENORE DI SMA KOTA PALEMBANG - Heni Sumastri; Nesi Novita (ABDIKEMAS: Jurnal Pengabdian Kepada Masyarakat, 2023)
This Community Service activity aims to utilize yoga child pose to reduce menstrual pain in young women. The benefit of the program is to provide information and education to young women about yoga child pose so that it can be used as an alternative method of reducing menstrual pain besides taking medication. to adopt policies on UKS activities, especially those related to menstrual pain in young women and with movement guidelines (SOP) and in dealing with adolescents who experience menstrual pain. By holding yoga child pose training, young women can do child pose yoga movements independently to deal with menstrual pain they are experiencing. Young women feel relaxed and comfortable with the child pose yoga movement, besides that it is also easy to do independently.